"I am the embodiment of an anorexic patient's worst fear": Severe obesity and binge eating disorder on a restrictive eating disorder ward. Issue 6 (10th September 2020) - Matthews, Kaitlyn N.; Psihogios, Maria; Dettmer, Elizabeth; Steinegger, Cathleen; Toulany, Alene
Summary: Adolescents who have been diagnosed with an eating disorder commonly have comorbid mental health conditions which have a significant impact on illness trajectory and may even limit access to effective treatment. Current models of eating disorder care focus mainly on treatment for patients diagnosed with restrictive eating disorders with fewer options available for those with binge eating disorder. We describe a case of an adolescent living with severe, complex obesity and binge eating disorder, presenting in a mental health crisis, admitted to an in‐patient unit primarily for patients being treated for restrictive eating disorders such as anorexia nervosa. This case report describes multiple challenges that arose in admitting such a patient on a ward specializing in the treatment of restrictive eating disorders and highlights the need for equitable and more accessible care for patients living with all types of eating disorders.